The effect of body positions on foot types: Considering body weight - Jonas A. Akambase; Tatyana V. Kokoreva; Olga A. Gurova; Joseph A. Akambase (Elsevier, 2019)
Introduction: This study had two objectives. First, to determine the prevalence of the various foot types based on height of the medial longitudinal arch. Second, to examine if a change in body positions has an associate effect on the anthropometric parameters of the foot types. Material and methods: A total number of 98 men between the ages of 18-25 were studied. The prevalence of normal foot, high-arched foot and flatfoot, was determined using an electronic plantogragh. The foot parameters were measured at sitting position, bipedal position (standing on two legs) and unipedal position (standing on one-leg). The data obtained was analyzed using excel. Results: The present work shows a significant change in foot width, Shtriter index, and the total square area of the foot across the various foot types with respect to change in body positions. Conclusion: In conclusion, the impact of body weight on foot varies at different body positions. The load-bearing capacity of the foot changed with respect to the weight of the body and this resulted a significant changes in the anthropometric parameters of high-arched and normal arched foot unlike flatfoot which recorded slight changes in it's anthropometric parameters. Keywords: Foot, Body weight, Body position, Foot parameters, Plantar pressure, Load-bearing